Undernutrition as Risk Factor of Hydrocephalus Prevalence in Children with Tuberculous Meningitis - Sinaga, John Patria Maruli; Risan, Nelly Amalia; Gamayani, Uni (Althea Medical Journal, 2017)
Background: Hydrocephalus is the most frequent neurological complication in children with tuberculous meningitis. Tuberculosis infection cannot be separated from nutritional status. Children with undernutrition have decreased immunity thus could affect clinical manifestation of tuberculous meningitis. This study was conducted to identify the relationship between undernutrition and the prevalence of hydrocephalus in tuberculous meningitis.Methods: An analytic observational study was carried out to 38 medical records of children with tuberculous meningitis in Dr. Hasan Sadikin General Hospital from 2007 to 2015. Variables that were studied included gender, age, advanced stage of disease, motoric paralysis, history of seizure, nutritional status and hydrocephalus. The collected data were analyzed using Chi-Square test. Results: Out of 21 subjects with undernutrition, 11 subjects were found to have hydrocephalus. The analysis using chi-square was statistically significant (p=0.009). Prevalence ratio=4.45 (CI 95% 1.14â45.43), meaning tuberculous meningitis children with undernutrition were at risk of hydrocephalus 4.45 times greater than children with normal nutritional status.Conclusions: Undernutrition may increase the risk of hydrocephalus in children with tuberculous meningitis. [AMJ.2017;4(1):143â7]Â DOI:Â 10.15850/amj.v4n1.1036